1998
DOI: 10.1055/s-2007-995851
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis: Coagulation and Fibrinolysis

Abstract: Tissue factor (TF) protein was overexpressed by macrophages and smooth muscle cells (SMCs) and deposited in the extracellular matrix of atherosclerotic intimas, probably resulting in enhanced procoagulant activity and the intimate participation in either thrombus formation or intimal fibrin deposition after the exposure of flowing blood and permeated fibrinogen to TF in atherosclerotic lesions. On the other hand, APO(a) was localized both in the stroma and within some macrophages. Fibrin deposition, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…21,24,[29][30][31][32] Activation of platelets and coagulation cascade triggered by atherosclerosis that causes fibrin turnover is the basis of pathogenesis consequently. [33][34][35][36] Diabetes mellitus is associated with increased levels of procoagulant factors. 37 Dyslipidemia is associated with hypercoagulability, endothelial dysfunction, and increased platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…21,24,[29][30][31][32] Activation of platelets and coagulation cascade triggered by atherosclerosis that causes fibrin turnover is the basis of pathogenesis consequently. [33][34][35][36] Diabetes mellitus is associated with increased levels of procoagulant factors. 37 Dyslipidemia is associated with hypercoagulability, endothelial dysfunction, and increased platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced platelet activation could imply less platelet impairment and less risk of bleeding episodes since there are fewer functionally exhausted platelets circulating in the blood stream. In addition, during the progression of the atherosclerotic disease, the vascular intima becomes more thrombotic than with nondiseased arteries, not only as a result of the procoagulant and hypofibrinolytic activities going on in the subendothelial matrix and atheromatous gruel, but also due to any endothelial injuries resulting from rupture or ulceration of the atheromatous plaques [39]. Sueishi et al [39]have demonstrated that in the atheromatous plaque tissue factor activity, assessed as factor X activation, is overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in lipolytic activity related to cyclic heparinization could be a further possible mechanism: cyclical and prolonged SH treatment activating lipoprotein lipase (LPL) causes a progressive decrease in lipolytic activity and accumulation of chilomicrons [25, 38]. Liu et al [39]have shown that LMWH has a lower affinity to LPL. This does not result in any lower ability to release LPL from endothelial binding sites in peripheral tissues, but mainly in a lesser ability of LMWH to prevent hepatic clearance of LPL [38].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] A role of this prothrombotic state in promoting venous thrombosis is plausible, on the basis of the assumption that activated platelets and coagulation factors appear in the slowflowing venous system. High d -dimer levels have been found to be associated with an increased risk of venous thromboembolism 37,38 and recurrent venous thromboembolism.…”
Section: Additional Observationsmentioning
confidence: 99%
“…[13][14][15][16] Furthermore, atherosclerosis is associated with activation of both platelets and blood coagulation as well as an increase in fibrin turnover, which can lead to thrombotic complications. [17][18][19][20][21][22][23] In subjects without symptomatic atherosclerosis, carotid plaques are considered a reliable marker of arterial disease elsewhere in the circulation. [24][25][26][27][28] To determine whether an association exists between asymptomatic atherosclerotic disease and the risk of venous thromboembolism, we assessed whether vessel-wall plaques were present and, if so, quantified them by means of carotid-artery ultrasonography in a consecutive series of patients with acute venous thrombosis and in a control group of subjects without thrombosis.…”
mentioning
confidence: 99%